MDG Oriented Sector and Poverty Reduction Strategies : Lessons from Experience in Health - Foster, Mick (World Bank, Washington, DC, 2013)
This review is a contribution to the debate on how to achieve and sustain the health-related Millennium Development Goals. It identifies ways in which government planning and budget processes and the management and delivery of external support can be more effective in supporting the goals, based on a review of how the health MDGs are being taken forward in a sample of low-income countries.